2011
DOI: 10.3389/fnhum.2011.00125
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Central Luminance Edge is Crucial for the Craik-O?Brien-Cornsweet Effect

Abstract: The Craik-O’Brien-Cornsweet (COC) effect demonstrates that perceived lightness depends not only on the retinal input at corresponding visual areas but also on distal retinal inputs. In the COC effect, the central edge of an opposing pair of luminance gradients (COC edge) makes adjoining regions with identical luminance appear to be different. To investigate the underlying mechanisms of the effect, we examined whether the subjective awareness of the COC edge is necessary for the generation of the effect. We man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For the current purposes, the results from Masuda et al (2011) indicate that on the one hand early visual regions can process Cornsweet circles even when suppressed from awareness. On the other hand, the experiments reported by Masuda et al (2011) reinforce the suggestion that top–down signals associated with conscious awareness appear to be necessary for higher-order processing of Cornsweet circles as required for aftereffects.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…For the current purposes, the results from Masuda et al (2011) indicate that on the one hand early visual regions can process Cornsweet circles even when suppressed from awareness. On the other hand, the experiments reported by Masuda et al (2011) reinforce the suggestion that top–down signals associated with conscious awareness appear to be necessary for higher-order processing of Cornsweet circles as required for aftereffects.…”
Section: Discussionmentioning
confidence: 73%
“…It is possible that although retinal inputs from the suppressed eye reached at least as far as V1, the current results may reflect the inability of the Cornsweet illusion to be detected without awareness rather than an absence of size aftereffects per se . Indeed, Masuda et al (2011) presented the edge of a Cornsweet illusion to participants under backward masking and CFS conditions and revealed that one must have a conscious awareness of the edge to experience a real-time illusion of differing luminance either side of the edge. More critically, in a separate adaptation experiment, the authors briefly applied CFS to the edge of the illusion and then had participants view a gray background.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for the gradients near the border, the two rectangles are equiluminant. If one covers the border between the rectangles, say with a pencil, the illusion disappears, indicating the importance of the luminance contrast-defined border 5 .…”
Section: Introductionmentioning
confidence: 99%